X10 : extended eco touring coupe / Iman NurHakim Samsudin - Samsudin, Iman NurHakim (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
XI0 - Extended Eco Touring Coupe have 2 mode drive consist of autonomous and sports mode to enhanced users experience in terms of dynamic driving which is different driving conditions. It is called “extended” because due to its long wheelbase which is 5.20m. The objective is to give users the maximum amount of comfort. XI0 is inspired by the combination of Mazda and Porsche design language.